Meloidogyne hapla, the Northern Root-Knot Nematode, in Florida Strawberries and Associated Double-Cropped Vegetables - Johan Desaeger (EDIS)
Northern root-knot nematodes (Meloidogyne hapla) are rather uncommon nematode parasites of strawberries and vegetables in Florida, but when present they are capable of causing significant crop loss. Root-knot nematodes are largely unknown to strawberry growers in Florida and very little is known about their biology and behavior in the state. This 5-page fact sheet written by J. Desaeger and published by the UF/IFAS Department of Entomology and Nematology is intended to educate and provide information on this nematode to researchers, Extension agents, growers, industry representatives, and other stakeholders in the strawberry and vegetable community. http://edis.ifas.ufl.edu/in1224